TERAPI PSORIASIS DI MASA PANDEMI COVID-19 (Media Dermato Venereologica Indonesiana, 2023)
Psoriasis is a chronic residive inflammatory skin disease caused by an autoimmune process. The worldwide prevalence of psoriasis ranges from 2-3% with the prevalence in Asia tends to be low, which is less than 0.5%. Psoriasis consists of erythematous scaly plaques and occurs most commonly on the elbows, knees, scalp, and lower back. Because of the reported frequent recurrences, psoriasis requires maintenance therapy in the form of systemic therapy such as retinoids, methotrexate, alefacept, and efalizumab. Coronavirus disease 2019 (COVID-19) is a respiratory infection caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and is highly contagious. The COVID-19 pandemic has a negative impact on psoriasis management and healthcare delivery. Infection of COVID-19 and its related medications can also affect the clinical severity and exacerbation in patient with psoriasis. Inadequate management of COVID-19 can trigger a cytokine storm and cause acute respiratory distress syndrome (ARDS), sepsis, and other complications. COVID-19 patients who experience a cytokine storm with elevated IL-6 and IL-17 may potentially experience psoriasis exacerbations. Biological therapy for psoriasis during pandemic should be carefully considered according to the individual patient’s condition.